Literature Review: The Influence of Forensic Audit, Independence, Auditor Competence, Experience, and Professionalism of Auditor on Fraud Disclosure - Triya Vebrianty; Dinda Rinata; Desy Sarina Br Barutu; Handriyani Dwilita (CV. AFDIFAL MAJU BERKAH, 2025)
An auditor with sufficient ability and skill can detect early signs and uncover cases of fraud. Along with technological advances and increasingly sophisticated fraud tactics, the need for forensic audits, auditor independence, auditor competence, auditor experience and auditor professionalism is also increasing. Forensic audit aims to minimize the opportunity factor for fraud by irresponsible parties. Independent auditors must be able to reveal fraud without being influenced by other parties. Adequate competence allows auditors to perform their duties effectively in disclosing fraud. Experienced auditors have a high probability of recognizing fraud patterns and auditors who are professional and compliant with audit procedures will be more effective in disclosing fraud. This article uses qualitative methods and literature research. This research involves reviewing theories and examining relationships or influences between variables through books and journals, both offline and online. The research findings, based on a review of several previous studies, show that forensic auditing, independence, auditor competence, experience and auditor professionalism have a positive effect on fraud disclosure.